Update on selective treatments targeting neutrophilic inflammation in atherogenesis and atherothrombosis - Quinderé, Ana Luíza Gomes; Benevides, Norma Maria Barros; Carbone, Federico; Mach, François; Vuilleumier, Nicolas; Montecucco, Fabrizio (Thrombosis and Haemostasis, 2014)
Atherosclerosis is the most common pathological process underlying cardiovascular diseases. Current therapies are largely focused on alleviating hyperlipidaemia and preventing thrombotic complications, but do not completely eliminate risk of suffering recurrent acute ischaemic events. Specifically targeting the inflammatory processes may help to reduce this residual risk of major adverse cardiovascular events in atherosclerotic patients. The involvement of neutrophils in the pathophysiology of atherosclerosis is an emerging field, where evidence for their causal contribution during various stages of atherosclerosis is accumulating. Therefore, the identification of neutrophils as a potential therapeutic target may offer new therapeutic perspective to reduce the current atherosclerotic burden. This narrative review highlights the expanding role of neutrophils in atherogenesis and discusses on the potential treatment targeting neutrophil-related inflammation and associated atherosclerotic plaque vulnerability.
Keywords: Atherosclerosis; inflammation; neutrophil